The Early Development of Sunnism and its Relation with Javanese Sufis - Abd. Rachman Mas'ud (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
This study is tracing the origins of early Sunnism and its relation with Javanese Sufis. Based on  primary sources, it is not useless to trace the origins of Sunnism back to the seventh century. By this quest, the portrait of later Sunnism will be, at least, better understood. Besides, following this framework enables one to understand how the Sunnis viewed their own history. Ibn Taimiyya, a very prominent Sunni scholar, for instance, claims that the Ahl al-Sunna wa al-Jama`a is an eminent classic ma©hab (ma©hab al-q±dim). It existed before Allah created Abu Hanifa, Malik, Syafi`i, and Ahmad bin Hanbal. Indeed it belongs to the mazhab of certain A¡¥±b who consistently emulated the Prophet. Those who opposed the Jama`a deserved to be called mubtadi`µn.